Simulation modeling and analysis of productivity Enhancement in manufacturing company using arena Software - Siti Hartini , Embong @ Ab Wahab (2013)
Every manufacturing company wants to improve and adapt their operating system in order to survive the industry competition. In manufacturing organizations, to improve their system it might mean to reduce the operating costs that come from the wastes in production line. By using the ARENA simulation in this study, the productivity improvement can be experimented without physically affect the real system and reduced the cost because designing, building, testing, redesigning, rebuilding and retesting can be an expensive project. This study focus on the flow in the production line processes in one piston manufacturing company. The existing plant layout was studied and formulated into ARENA simulation software as well as to enhance the productivity rate by improving certain parameters. The problems identified in this production line are the effect of the bottleneck process which resulting some idle time in some workstations and the increased piston demands from the customers. The data acquired and was translated into the ARENA simulation software and studied in order to simulate the existing plant layout design. Hence, the problems occurred in the production line can be seen clearly to determine room for productivity improvement. New designs are proposed by constructing several models to acquire the best solution to improve productivity capacity and meet the forecasting demand of customer. In these proposed models, the parameters of the actual system are modified accordingly in the terms of material handling such as human resources, machine cycle time, the number of machines, shape and area of plant layout. From the simulation results, the significant contribution factor that influenced the rate of productivity was by adding certain machines to do the same process to cover the buffer while the material handling did not have a huge effect on the production line.